Peran Iman Kristiani terhadap Penggunaan Ilmu Pengetahuan Teknologi dan Seni oleh Generasi Muda Kristen di Lingkungan Fakultas Bahasa dan Seni - Dina Octavia Siburian; Naomi Octa M Lumban Tobing; Nova Ritonga; Shennyin Sella Ester Octavia (Sukacita : Jurnal Pendidikan Iman Kristen, 2025)
The development of science, technology, and the arts (IPTEKS) presents both challenges and opportunities, particularly for young Christians in the Faculty of Languages and Arts. This study explores the role of Christian faith in shaping how young Christians engage with IPTEKS, focusing on the integration of faith-based values in artistic creation, scientific application, and technological use. Using qualitative descriptive methods, the research involved interviews, observations, and documentation from Christian students in various art and education programs. The findings suggest that Christian faith provides a moral, ethical, and spiritual foundation for the responsible use of IPTEKS. In the arts, faith motivates students to create works that serve as ministry and testimony. In science, it encourages knowledge application for service and glorifying God. In technology, faith serves as a moral filter for the positive use of digital media. Key scriptures, including Proverbs 1:7, Colossians 3:23-24, and Romans 12:2, reinforce that IPTEKS should be utilized to honor God and serve others. This study highlights the need for faith development in academic settings, ensuring that young Christians engage with IPTEKS wisely, ethically, and in alignment with Christian values.